Analysis of Project Delay Using the Fault Tree Analysis (FTA) Method in Rising Building Projects - Asyari, Saidatul Alfena Putri; Putra, I Nyoman Dita Pahang (Universitas Negeri Padang, 2023)
A job on a construction project can affect delays throughout the project. Every construction project has a specific plan and schedule for when to start when to finish, how to schedule, and how to provide resources. There should be no delays in implementation because they will result in increased project costs. However, there was a delay in the performance of the lecture building construction project with the Faculty of Engineering UPN